If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 5) + 5 = 21 + -1x Reorder the terms: 4(5 + x) + 5 = 21 + -1x (5 * 4 + x * 4) + 5 = 21 + -1x (20 + 4x) + 5 = 21 + -1x Reorder the terms: 20 + 5 + 4x = 21 + -1x Combine like terms: 20 + 5 = 25 25 + 4x = 21 + -1x Solving 25 + 4x = 21 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 25 + 4x + x = 21 + -1x + x Combine like terms: 4x + x = 5x 25 + 5x = 21 + -1x + x Combine like terms: -1x + x = 0 25 + 5x = 21 + 0 25 + 5x = 21 Add '-25' to each side of the equation. 25 + -25 + 5x = 21 + -25 Combine like terms: 25 + -25 = 0 0 + 5x = 21 + -25 5x = 21 + -25 Combine like terms: 21 + -25 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8
| -2x-3y=15x+12 | | 2x-(3-3x)=12 | | (5x+10)(4x-10)= | | x+(12+x)=150 | | -5r-18r-(-16r)=14 | | secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 |